KEPENTINGAN AMERIKA SERIKAT MENYEPAKATI TRANS PACIFIC PARTNERSHIP (TPP) DI KAWASAN ASIA TENGGARA TAHUN 2011-2015 - Muhammad Nuzulurridha; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research describes about the United State of America’s Interest towards to Trans Pacfic Partnership (TPP) in Southeast Asia region. Trans Pacific Partnership is an agreement about free trade area and want to make pacific area as the center of international commerce line. In the 2011 the US goverment decided to get involved in TPP agreement, then try to make TPP agreement as priority for enhance their export-import also as a place to protecting their businesses in the foreign states.At the same time, while US government still trying to fixing their economic problems, China already spreads their influences in southeast asia, especially in economic sector. China already made few agreements between Southeast Asia States and China such as ACFTA and RCEP.The theory that applied on this research are neo-liberalism, level analysis of Nations-states, national Interest and concept of economic international politicNational Interest is a concept that every state that should have where it can give big contribution for establishment point of views the state about the external environment.The study found that the reason of US government agreed about TPP agreement is because the US wants to compete with the dominancy of economic China in Souteast Asia. Because the highest dominancy china in Souteast Asia makes the US infulences in Southeast Asia getting low. So that US wants to increasing their hegemony in the southeast Asia through Trans pacific partnership (TPP).Keywords : United State of America, Trans Pacific Partnership, China, and Southeast Asia